What's better than a biscuit?: Gourmetization and the transformation of a Southern food staple. Issue 3 (3rd July 2021) - Harris, Deborah A.; Phillips, Rachel
Abstract: In this article, we applied Wendy Griswold's concepts of cultural objects and the cultural diamond to examine how a specific food—Southern style biscuits—underwent gourmetization. We provide evidence from observations of seven well-known gourmet biscuit restaurants, as well as a content analysis of their websites, Instagram accounts, and media coverage to understand how some establishments were able to position biscuits as a new gourmet food. We found that food producers combined upscale and exotic ingredients and recipes to create new ways of enjoying biscuits, as well as harnessed the power of social media to create excitement for their products. Simultaneously, the association of biscuits with the home and family recipes provided a form of cultural legitimacy and helped set these restaurants apart from fast food and its unhealthy, placeless reputation. Cultural tastemakers, including food writers and journalists, have aided in the rise of Modern Southern cuisine, which allows traditional Southern foods like biscuits to be viewed as higher in status. Customers, particularly those engaged in food-based tourism and those living in gentrifying areas have also helped encourage gourmetization through their willingness to pay higher prices and to embrace food as spectacle.